Clinical, computed tomographic, surgical findings and outcome in dogs with sublumbar abscessation: 16 cases (2013‐2019). (11th December 2021) - Jacques, D.; Meige, F.; Thierry, F.
Abstract : Objectives: To describe the clinical presentation, CT imaging findings, surgical treatment and long‐term outcome in dogs with sublumbar abscessation. Materials and Methods: Medical records of dogs treated for sublumbar abscessation between 2013 and 2019 were retrieved. Criteria for inclusion were a diagnosis of sublumbar abscessation, complete patient history, pre‐operative CT imaging, blood work, bacteriology results, record of the surgical treatment, post‐operative care and outcome. Results: Sixteen dogs were included in this study with a median follow‐up period of 36 months (15/16). Clinicals signs included flank or lumbar soft tissue swelling (12/16), lumbar pain (11/16), hyperthermia (8/16), a cutaneous discharging sinus (5/16) and lethargy (5/16). CT findings were: abscesses of varying size localised in the psoas muscles (16/16), spondylitis (12/16), vertebral osteomyelitis (6/16), discospondylitis (2/16) and epidural inflammation (8/16). Thoracic lesions were present in eight of 12 dogs. Exploratory surgery was performed in 16 dogs via a midline celiotomy in 15 of 16 and a lateral approach in one of 16 cases. The surgical approach was selected based on the location of the draining tracts detected on CT imaging. Vertebral body curettage was performed in five of 16 cases with lesions identified on CT. Vegetal foreign material was found in seven of 16 dogs. Of the 15 animals with long‐term follow‐up, 13 had no signs of recurrence. Clinical Significance: Surgical treatment of sublumbar abscessation resulted in a good long‐term outcome when CT was used to guide the surgical approach and to plan the procedure. Our study highlights common vertebral and epidural lesions associated with sublumbar abscesses with a prevalence of 87.5%.